Analysis of Students' Science Process Skills Assisted with Digital Worksheets on Temperature and Heat Materials - Algiranto Algiranto; Rikardus Feribertus Nikat; Sulistiyono Sulistiyono (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2022)
This research aimed to determine the analysis of process skills on the digital worksheet for class X MA Almunawaroh material temperature and heat. This study uses a quantitative descriptive method based on 6 indicators of science process skills, namely formulating problems, making observations, formulating hypotheses, testing hypotheses through experiments, analyzing to make conclusions, and communicating results. The material analyzed in the digital worksheet is temperature and heat in terms of explaining concepts, student activities, and using digital worksheets. The results of this study indicate that the criteria for science process skills raise 6 indicators with varying percentages of concept explanations, student activities, and the use of digital worksheets. Each indicator obtained the percentage value of science process skills, namely: formulating problems (23.80%), conducting observations (14.20%), formulating hypotheses (26.20%), testing hypotheses through experiments (21.50%), analyzing to make conclusions (9.58%), communicate results (4.72%). Based on all the digital worksheet-assisted learning series, it can be concluded that science process skills can be measured and trained properly based on 6 indicators of science process skills in learning temperature and heat in class X MA Almunawaroh.